Fast Mapping Skills in the Developing Lexicon. - Gershkoff-Stowe, Lisa; Hahn, Eric R. (Journal of Speech, Language & Hearing Research, 2007)
Purpose: This preliminary investigation was a longitudinal study of fast mapping skills in normally developing children, 16-18 months of age. The purpose was to examine the effects of practice on the accessibility of words in lexical memory. Method: Eight children were taught the names of 24 unfamiliar objects over 12 weekly training sessions. The amount of practice children had with individual words varied as a function of session. Data were compared to a control group of children—matched on productive vocabulary—who were exposed to the same experimental words at the first and last sessions only. Results: The results showed that for children in the experimental group, extended practice with a novel set of high-practice words led to the rapid acquisition of a second set of low-practice words. Children in the control group did not show the same lexical advantage. Conclusions: The data suggest that learning some words primes the system to learn more words. Vocabulary development can thus be conceptualized as a continual process of fine-tuning the lexical system to enable increased accessibility to information. Implications for the treatment of children with word-finding difficulties are considered. Reprinted by permission of the publisher.